2022
DOI: 10.3390/mi13091545
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Properties of a Twisted Double Planetary Chaotic Mixer: A Three-Dimensional Numerical Investigation

Abstract: In this study, a numerical investigation based on the CFD method is carried out to study the unsteady laminar flow of Newtonian fluid with a high viscosity in a three-dimensional simulation of a twisted double planetary mixer, which is composed of two agitating rods inside a moving tank. The considered stirring protocol is a “Continuous sine squared motion” by using the dynamic mesh model and user-defined functions (UDFs)to define the velocity profiles. The chaotic advection is obtained in our active mixers by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…For example, Ser-Giacomi et al [19] investigated fluid transport within various regions of the fluid area by Lyapunov exponents (LEs). In addition, LE was used to assess the strength of stirred mixing chaoticity [20] or to evaluate the mixing quality in a planetary mixer [21]. Christov et al [22] used SFs to evaluate the mixing deformation of fluids and showed that the first and second LE could explain the rates of SF.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ser-Giacomi et al [19] investigated fluid transport within various regions of the fluid area by Lyapunov exponents (LEs). In addition, LE was used to assess the strength of stirred mixing chaoticity [20] or to evaluate the mixing quality in a planetary mixer [21]. Christov et al [22] used SFs to evaluate the mixing deformation of fluids and showed that the first and second LE could explain the rates of SF.…”
Section: Introductionmentioning
confidence: 99%